THEORIES ON THE ORIGIN OF LANGUAGE - Inatova Jasmina Sohib qizi (International Journal of Literature and Language Studies, 2026)
This theoretical-scientific article provides a comprehensive analysis of the main theories, scientific hypotheses, and modern research directions dedicated to one of the most complex and mysterious problems in human history—the origin of language (glottogony). Language is not merely a means of information exchange, but the highest product of human cognition, social structure, and biological evolution. Consequently, the study of language origins is conducted at the intersection of philology, anthropology, neurobiology, archaeology, and cognitive sciences.